Misconceptions in Regional Geography Adventure - (:unkn) unknown (MARMARA UNIV, 2016)
In geographical terms, the region is each of the areas of a city or a piece of land divided with the aim of intentional documenting according to a designed plan based on industry, agriculture, housing, management or commerce. It is a piece of land where natural features, population structure, resources showing similarity deemed to be useful to plan this piece of land as a unity and it is a bounded territory. Region types will vary according to sciences. Many scientists and officials such as geographers, historians, sociologists, mathematicians, economists, planners, managers, educators employ the concept of region and each of them has a different understanding of region. It is not possible to think that there are geographical regions in unity in all respects not only in Turkey but also in anywhere in the world. Consequently, geographical region is imaginary. Perhaps one or two geographic features can be similar in any given place. For instance, climate and vegetation characteristics might match but it is not always the case. However, it has been created some regions since 1905 and distinguished several regions in the world scale. Those regions named as natural regions but other sub-units do not match so, it is faulty to call them as natural regions completely. Searching for geographic regions in a country is a useless work. On the other hand, it would be very wrong to identify regions based on natural or human geographical characteristics. Therefore, it is fictitious to speak about 7 geographic regions in Turkey and it is completely wrong. Turkey is a unity.
Keywords: Geography; region; region division; regional misconception